2009
DOI: 10.1190/1.3158051
|View full text |Cite
|
Sign up to set email alerts
|

Improved geometric-spreading approximation in layered transversely isotropic media

Abstract: A new approximation ͑direct approximation͒ for the relative geometric spreading of qP-waves in a layered transversely isotropic medium uses three traveltime parameters: twoway vertical traveltime, normal-moveout velocity, and the heterogeneity coefficient. These traveltime parameters, which can be estimated in velocity analysis, enter the parameters of geometric-spreading approximation. The new approximation is based on the acoustic approximation for a single-layer vertical transversely isotropic ͑VTI͒ medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The DRA for the relative geometrical spreading (LN) is given by Stovas and Ursin () scriptLN(DRA)=scriptL01+A2x̂2+A4x̂41+B2x̂2,where the zero‐offset term scriptL0=t0bold-italicvn2, A 2 and A 4 are the second‐ and fourth‐order coefficients in Taylor series computed at the zero‐offset, A2=1+8η,A4=9η1+4η,and the coefficient B 2 can be obtained from the slope of LN at the infinite offset limit given by B2=9ηfalse(1+4ηfalse)1+2ηfalse(1+8ηfalse)1+2η1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The DRA for the relative geometrical spreading (LN) is given by Stovas and Ursin () scriptLN(DRA)=scriptL01+A2x̂2+A4x̂41+B2x̂2,where the zero‐offset term scriptL0=t0bold-italicvn2, A 2 and A 4 are the second‐ and fourth‐order coefficients in Taylor series computed at the zero‐offset, A2=1+8η,A4=9η1+4η,and the coefficient B 2 can be obtained from the slope of LN at the infinite offset limit given by B2=9ηfalse(1+4ηfalse)1+2ηfalse(1+8ηfalse)1+2η1.…”
Section: Methodsmentioning
confidence: 99%
“…Note that the coefficients C 2 and C 4 in the approximation are only defined by fitting the subsequent term for the asymptotic behaviours at the infinite offset limit for the relative geometrical spreading. By setting C4=2C2, the GMA form approximation (equation ) is reduced to the ration form (equation ) defined by Stovas and Ursin (). When setting η=0 for elliptical anisotropic model, all approximations (rational and GMA form) result in the same expression with the reference one regardless of direct or indirect type shown by scriptLN=scriptL0false(1+x̂2false).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different from the indirect type approximation, which is approximating the traveltime for geometric spreading approximation, the direct-type approximation is computed by approximating the geometric spreading term directly from the exact parametric equations obtained from dynamic ray tracing. The first example of this comparison between indirect and direct type approximation is done by Stovas and Ursin (2009), who developed the rational type of approximation in direct form. They showed that the direct rational approximation is simpler and more accurate than the indirect counterpart for a homogeneous and multilayered VTI model.…”
Section: Introductionmentioning
confidence: 99%